2018
DOI: 10.1111/jcpp.12921
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a computerised test of attention and activity (QbTest) on diagnostic decision‐making in children and young people with suspected attention deficit hyperactivity disorder: single‐blind randomised controlled trial

Abstract: Background: Diagnosis of attention deficit hyperactivity disorder (ADHD) relies on subjective methods which can lead to diagnostic uncertainty and delay. This trial evaluated the impact of providing a computerised test of attention and activity (QbTest) report on the speed and accuracy of diagnostic decision-making in children with suspected ADHD. Methods: Randomised, parallel, single-blind controlled trial in mental health and community paediatric clinics in England. Participants were 6-17 years-old and refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 40 publications
(56 reference statements)
0
60
0
Order By: Relevance
“…The completion and return of study outcome measures by primary care-givers and teachers was similar across measures, although returns by teachers were affected by the timing of school holidays, particularly the long (6-week) summer holidays. Our response rates were lower than we would anticipate based on similar trials [22] however, during interviews the primary care-givers acknowledged that although the trial included several questionnaires, they were not unduly burdened by completing them. Based on our previous experience of successful trials we would implement the following strategies to facilitate completion rates: conduct measures online with researcher telephone support where needed, including out-of-hours telephone appointments, and provide personalised thank you messages when measures are complete.…”
Section: Outcome Measuresmentioning
confidence: 59%
See 1 more Smart Citation
“…The completion and return of study outcome measures by primary care-givers and teachers was similar across measures, although returns by teachers were affected by the timing of school holidays, particularly the long (6-week) summer holidays. Our response rates were lower than we would anticipate based on similar trials [22] however, during interviews the primary care-givers acknowledged that although the trial included several questionnaires, they were not unduly burdened by completing them. Based on our previous experience of successful trials we would implement the following strategies to facilitate completion rates: conduct measures online with researcher telephone support where needed, including out-of-hours telephone appointments, and provide personalised thank you messages when measures are complete.…”
Section: Outcome Measuresmentioning
confidence: 59%
“…Although comparatively less researched than its use for diagnosis, qualitative findings from a recent randomised controlled trial (RCT) indicate the potential for QbTest to aid medication management [21,22]. Clinician interviews have identified that the QbTest is useful in supporting their confidence in starting medication, choosing suitable titration schedules, communicating to families/schools about medication efficacy, and promoting medication adherence [21].…”
Section: Introductionmentioning
confidence: 99%
“…Current service provision for ADHD in the CYPSE is ad hoc and uncoordinated. There is growing evidence within community settings30 32–34 that QbTest has the potential to significantly improve the current assessment pathway having a direct impact on young people’s health, service delivery and criminal justice outcome.…”
Section: Discussionmentioning
confidence: 99%
“…At 6 months, 76% of those with a QbTest report had received a diagnostic decision, compared with 50% without a QbTest report. QbTest reduced appointment length, increased clinicians’ confidence in their diagnostic decisions and doubled the likelihood of excluding ADHD 33…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation